Field experimental research on retarding frosting and improving defrosting performance of air source heat pumps through variable frequency technology. (1st April 2023) - Wu, Chunling; Wang, Zhichao; Li, Xiaofeng; Xu, Zhaowei; Xu, Ce; Yang, Yingxia; Zhao, Wenyuan; Wang, Yichao
Abstract: Frosting is one of the major factors affecting the performance of air source heat pumps (ASHP). Two almost identical ASHP systems, equipped with variable frequency and constant frequency compressors respectively, were tested in North China to analyze the influence of frequency conversion technology on frosting. The whole frost-defrost circle is divided into three intervals, defrosting period, frost-free period and a frosting period. The results indicate that frequency conversion technology can effectively extend frost-free period and shorten defrosting period. For whole heating season, variable-frequency units experience longer durations of frost-free period, which increases the overall performance of units by 4%. When the ambient temperature ranges from −10 °C to 12 °C, the defrosting duration of variable-frequency units is only 26% of that of fixed-frequency units, which makes the performance of variable-frequency units 5% higher. It means that shorter defrosting times and longer frost-free periods resulted in an average 9% variable-frequency unit performance increase in comparison with fixed-frequency units. Meanwhile, variable frequency units can effectively enhance the part-load performance by 7%. Through the application of frequency conversion technology can improve performance by 16%. Highlights: Variable-frequency and fixed-frequency ASHPs are carried out in similar conditions. The defrosting times of variable-frequency units is 26% of fixed-frequency units. The COP of variable-frequency units is 9% higher due to less defrosting energy loss. The frequency conversion technology can save 16% of energy consumption.